The Spread of Salafi Ideology in Digital Media: Exploring Al-Qur’an Interpretation in rumaysho.com - Sakinah, Ekatul Hilwatis; Mh, Syahidil Mubarik (Faculty of Ushuluddin, Adab, and Da'wah, State Islamic University of Palangkaraya, 2024)
This article aims to analyze the pattern of interpretation of the Qur'an and the ideology behind the interpretation on rumaysho.com. This article is library research with primary data sources from rumaysho.com posts on shirk, takfiri, and leadership. Secondary data sources come from tafsir books and articles relevant to the study's focus. The data obtained were analyzed using three stages: data reduction, data display, and conclusions. Analysis of the data obtained shows that the pattern of interpretation of shirk, takfiri, and leadership in rumaysho.com uses the bil ma'tsur form with thematic methods and adabi al'ijtima'i style. Overall, Tuasikal's writings on rumaysho.com reflect an attempt to promote an understanding of Islam based on strict textual interpretation. The discourse used by Tuasikal is based on the puritanical Salafi ideology with its aim of purifying Islamic teachings and directing Muslims' understanding of practices that it considers authoritative. The dissemination of Salafi in rumaysho.com is also done by presenting and selecting references from Salafi ulama. The findings can contribute to developing digital interpretation by highlighting the dynamics of religious authority and perspectives on the use of digital media in conveying Islamic discourse.